Tantangan dan Peluang Pasar Modal Indonesia dalam Meningkatkan Minat Investasi di Era Digital - Malva Zaskia Putri; Dini Wulandari; Putri Amelia Aristawati; Esty Apridasari (Teewan Journal Solutions, 2025)
The Indonesian capital market is facing a digital era that brings various challenges as well as opportunities to increase public investment interest. Technological transformation, especially through digital platforms, has provided wider and more practical access for the public to invest. However, public participation is still low due to various factors such as lack of financial literacy, limited number of issuers and investment products, and the prevalence of unhealthy practices such as gorengan shares. This study uses a qualitative approach with analysis of relevant literature, and aims to provide an in-depth understanding of the actual conditions of the Indonesian capital market, the structural challenges faced, and potential strategies to encourage the growth of domestic investors. The results of the study show that with the support of inclusive policies, collaboration between stakeholders, and optimal use of digital technology, the Indonesian capital market has the potential to become one of the main pillars of inclusive and sustainable economic growth.